Occupational stress among academic women in Viet Nam - Le, Van Thanh (Curtin University, 2013)
The present research aims to bring deeper understanding and insight into the perceptions and experiences of women in relation to occupational stress, and associated coping mechanisms, in the unique cultural context of Vietnam. The study also examines differences in perceptions of occupational stress and the coping mechanisms across subgroups of women (age, education background, occupational roles & levels, marital status and experience) and makes a comparison with perspectives in other cultures.A qualitative, grounded theory approach was used to study occupational stress by collecting data from in-depth interviews with 42 academic women employed at Vietnamese higher education institutions to understand the meaning that these women attach to occupational stress; the nature and source of the occupational stress they experience; the impact of occupational stress on their lives; and the coping mechanisms they deploy in response to occupational stress.Cultural factors play an important role in occupational stress. Cultural factors influence experiences of occupational stress and the ways occupational stress is responded to. The Vietnamese context differs from other cultural contexts in the range of factors perceived as stressors for Vietnamese women.The study findings can be used to give voice to Vietnamese women experiencing occupational stress; to inform university policy makers with regard to occupational stress experienced by women in Vietnamese higher education; and to benefit scholars studying occupational stress in different cultural contexts via a conceptual consideration of the cultural aspects of occupational stress.The work adds to the few extant studies on occupational stress which have used grounded theory. By so doing, gaps in the existing grounded theory research on occupational stress are identified and proposals for future occupational stress research are put forward. This research is the first grounded theory study of occupational stress among women academics in Vietnam that determines that cultural factors play an important role in how women understand and respond to occupational stress and supports the growing evidence that occupational stress is common, global and varies between cultures.